Can the delta neutrophil ındex be used as a preliminary biomarker ın the evaluation of periodontal disease: a pilot study (Journal of Applied Oral Science, 2022)
Objective: Tissue destruction in periodontal diseases is related to inflammatory mediators in the host. However, it is unknown whether a relationship between delta neutrophil index (DNI) and neutrophil-lymphocyte ratio (NLR) in Stage 3 Grade A patients occurs. This cross-sectional study aimed to investigate the relationship between periodontal disease and DNI and NLR. Methodology: The study included 74 systemically healthy, non-smoking adults separated into 3 groups. Group 1: 26 subjects with good periodontal health, Group 2: 26 subjects with gingivitis, and Group 3: 22 subjects with Stage 3 Grade A periodontitis. After determining which group the patient will be included in, a clinical periodontal examination was made of each patient and pocket depth (PD), clinical attachment level (CAL), gingival index (GI), bleeding on probing (BOP) and plaque index (PI) parameters were measured. Venous blood samples were taken and examined with an automatic hematology analyzer for DNI, immature granulocytes (IG), NLR, C-reactive protein (CRP), procalcitonin, neutrophil count and lymphocyte count. Results: DNI, IG, CRP, and neutrophil count were observed to be highest in Group 3, followed by Group 2, and the difference between the groups in these parameters was determined to be statistically significant (p<0.001, p<0.001, p=0.046, p=0.016). DNI, IG, CRP and neutrophil count were observed to be positively correlated with periodontal parameters. Conclusion: The findings of this study support the role of DNI as a new biomarker for periodontal diseases. DNI may better reflect the systemic level of stage 3 grade A periodontitis than traditional inflammatory markers.